Endometrial cancer in a young lady - Yee Yee, Kyaing; Awi, Idi (Malaysian Medical Association, 2023)
Introduction: Endometrial cancer is the most common gynaecological cancer in developed countries and rapidly increasing together with the development of socioeconomic status and the prevalence of metabolic diseases. It is common in postmenopausal women but the incidence among young women is about 2 to 14%. Case Description: A 28-year-old single lady presented with abnormal uterine bleeding for 4 months. Her body mass index was 48.3 kg/m2 and investigations showed she had diabetes mellitus, hypertension, hyperlipidemia, mild ischemic heart disease, and obstructive sleep apnoea. Finally, she was diagnosed with endometrial cancer FIGO stage IA and treated with total abdominal hysterectomy, bilateral salpingooophorectomy, and pelvic lymph node dissection. Histopathology confirmed that it was grade 1 endometrial carcinoma, staged IA, with features of endometrial hyperplasia and atypia. Discussion: Endometrial cancer is usually diagnosed at the mean age of 68 years. Among many risk factors of endometrial cancer, components of metabolic syndrome are strongly associated with it. Young-aged endometrial carcinoma is not uncommon. According to the Asian data, among components of metabolic syndrome, obesity is a more prominent risk factor. Many studies showed metabolic syndrome caused the development of endometrial cancer by directly acting on tumour cells and regulating tumour environment. Some studies revealed that weight loss management could reduce the incidence of endometrial cancer and hyperplastic endometrium may be reversible. Therefore, many researchers conclude that early intervention of metabolic syndrome and a healthy lifestyle are important roles in the prevention and prognosis of endometrial cancer.